Causas de abandono del implante subdérmico utilizado como método anticonceptivo por las pacientes atendidas en el Hospital Universitario de Motupe, en el periodo de mayo - agosto 2014 - Cuenca Solórzano, Andrés Vinicio (2015)
I did a descriptive, prospective and transversal study on 102 users who withdrew the subdermal implant at University Hospital of Motupe in the May-August 2014; where it was determined in which the causes of abandonment of subdermal implant, the most common cause of abandonment, neglect sociocultural causes, the most common time of abandonment was determined to conclude the investigation and was developed and implemented a conference on the use and causes abandonment of subdermal implant. In the present study surveys, which prior authorization will informed consent patients were performed subdermal implants that were removed in outpatient clinics at University Hospital Motupe were used; where major cause of abandonment were first weight gain ; followed to a lesser extent dysfunctional bleeding and headache. The desire for a new pregnancy and contraception change were the most relevant to the socio-cultural causes abandonment of the method; in the time of most frequent abandonment of subdermal implant it was under one year. KEY WORDS Subdermal contraceptive implant, Causes of abandonment.